A business-cycle model with a modified cash-in-advance feature, government sector and one-period nominal wage contracts: the case of Bulgaria - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance; Vol 6 No 1 (2020): JMEF, Volume VI, Issue 1(10), Summer 2020DO - 10.14505/jmef.v6.1(10).02, 2020)
A business-cycle model with a modified cash-in-advance feature, government sector and one-period nominal wage contracts: the case of Bulgaria